The Medial Femoral Condyle Corticoperiosteal Free Flap for Frontal Sinus Reconstruction. Issue 3 (May 2017) - Pulikkottil, Benson J.; Pezeshk, Ronnie A.; Ramanadham, Smita R.; Haddock, Nicholas T.
Abstract : Abstract: Although the medial femoral condyle has been used for reconstruction in various areas of the body, to the authors' knowledge it has not been used for frontal sinus reconstruction. The authors describe a novel approach to a complex patient using the medial femoral condyle cortiocoperiosteal free flap to reconstruct an anterior frontal sinus defect in conjunction with a recalcitrant mucocele.